2020
DOI: 10.18865/ed.30.s1.229
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Biologic Predictors of Response Disparities to Atypical Antipsychotics among Blacks: A Quasi-Systematic Review

Abstract: Purpose: Management of schizophrenia among Blacks in the United States is af­fected by persistent disparities. This review explored response to atypical antipsychotics among Blacks compared with other groups to assess systematic variation that may con­tribute to disparities.Methods: We conducted a quasi-systematic review of studies reporting response to atypical antipsychotics among Blacks com­pared with other groups, including effects of genetic variation.Results: Of 48 identified research articles, 29 assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…For example, Blacks are more susceptible to certain ADRs, such as angiotensin converting enzyme (ACE) inhibitor‐induced angioedema and cough, thrombolytic‐associated intracranial hemorrhage, 17 drug‐induced liver injury, 18 and antipsychotic‐associated adverse effects. 19 Furthermore, differences in first‐line recommended antihypertensive therapy, increased occurrence of treatment‐resistant hypertension, 20 and reduced efficacy of antihypertensive therapy 21 in Blacks, have also been noted. Similarly, women are approximately two times more likely to experience, and be hospitalized for, an ADR compared to men.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Blacks are more susceptible to certain ADRs, such as angiotensin converting enzyme (ACE) inhibitor‐induced angioedema and cough, thrombolytic‐associated intracranial hemorrhage, 17 drug‐induced liver injury, 18 and antipsychotic‐associated adverse effects. 19 Furthermore, differences in first‐line recommended antihypertensive therapy, increased occurrence of treatment‐resistant hypertension, 20 and reduced efficacy of antihypertensive therapy 21 in Blacks, have also been noted. Similarly, women are approximately two times more likely to experience, and be hospitalized for, an ADR compared to men.…”
Section: Introductionmentioning
confidence: 99%
“…23,24,26 For example, Salama et al 26 recruited a 70% Hispanic or Latino and Black population to determine whether approved drugs or standard care were as efficacious in these groups in reducing the likelihood of disease progression to mechanical ventilation or death among hospitalized patients with COVID-19 pneumonia. Jerome et al 29 also highlighted the benefits of oversampling and reported that among 60% of studies assessed (n = 29/40), the inclusion of Black and White participants resulted in the ability to assess a modified and decreased response to antipsychotics among Black participants compared to White participants.…”
Section: Sex and Gendermentioning
confidence: 99%
“…Furthermore, there may be cultural differences in the placebo response. Placebo effects are dependent upon cultural expectations and beliefs; these are responsible both for the therapeutic effects of treatment but also have adverse effects [46].…”
Section: Ethnopharmacologymentioning
confidence: 99%